2023
DOI: 10.3390/pathogens12060821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Administration of Meglumine Antimoniate and Polyhexamethylene Biguanide Alone or in Combination with a Toll-like Receptor 4 Agonist for the Treatment of Papular Dermatitis due to Leishmania infantum in Dogs

Icíar Martínez-Flórez,
Maria Jose Guerrero,
Annabel Dalmau
et al.

Abstract: Papular dermatitis is a cutaneous manifestation of canine Leishmania infantum infection associated with mild disease. Although it is a typical presentation, nowadays, there is still no established treatment. This study evaluated the safety and clinical efficacy of local meglumine antimoniate, locally administered polyhexamethylene biguanide (PHMB) alone or PHMB in combination with a Toll-like receptor 4 agonist (TLR4a) for the treatment of papular dermatitis due to L. infantum and assessed parasitological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…Notably, dogs with papular dermatitis are markedly younger than their counterparts, boasting a median age of 6 months, with ages ranging from 3 months to 7 years. This is in line with previous studies, as papular dermatitis is consistently diagnosed in dogs under one year of age [ 39 , 48 , 49 ]. This has been theorized to be attributed to the condition’s propensity to manifest during the initial encounter between the parasite and the host’s immune system, making it more prevalent in young dogs, particularly in areas where the parasite is endemic [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Notably, dogs with papular dermatitis are markedly younger than their counterparts, boasting a median age of 6 months, with ages ranging from 3 months to 7 years. This is in line with previous studies, as papular dermatitis is consistently diagnosed in dogs under one year of age [ 39 , 48 , 49 ]. This has been theorized to be attributed to the condition’s propensity to manifest during the initial encounter between the parasite and the host’s immune system, making it more prevalent in young dogs, particularly in areas where the parasite is endemic [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…This particular clinical presentation is commonly associated with a robust and protective immune response. Notably, these dogs spontaneously resolve cutaneous lesions, as evidenced by long-term follow-up, which also indicates an absence of clinical relapse or the emergence of systemic clinical signs, and thus, they are more likely to be representative of an effective immune response and not just an early phase of the disease [ 39 , 45 , 46 , 47 , 49 ]. To further support this, the long-term follow-up in the current study showed that only three animals out of 25 were considered to get worse without systemic treatment, and the other 22 dogs resolved cutaneous lesions and remained healthy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations